Thermal study of clay bricks reinforced by sisal-fibers used in construction in south of Morocco - M. Ouakarrouch; K. El Azhary; M. Mansour; N. Laaroussi; M. Garoum (Energy Reports, 2020)
Clay is a local construction material used in a traditional building, it has many environmental, social and cultural benefits. The present research study focuses on improving the thermophysical properties of clay extracted from Erfoud city in the south-east of Morocco by incorporating natural additives such as sisal fibers. Several samples were prepared and their thermophysical properties were characterized experimentally using the steady state hot plate and the flash methods to estimate the thermal conductivity and the thermal diffusivity, respectively. The results showed~a significant~interest in the future use of this composite material in the construction buildings in order to ensure thermal comfort and reduce greenhouse gas emissions (CO2). The dynamic thermal simulation was performed of the traditional building Ksar Lamaadid in Erfoud city in order to get energy savings without affecting indoor~comfort~levels according to outside temperatures.
Keywords: 330; Clay-sisal fibers; Ecological composite materials; Greenhouse gas emissions; Thermal comfort; Thermophysical properties